Estimating output mix effectiveness: A scenario approach - Torbjørn Hanson (University of Oslo, Department of Economics, 2016)
The ability of public sector policy makers to prioritize has a huge impact on the effectiveness of public service provision. Public services can take the form of final outputs demanded by consumers or of intermediate outputs contributing to a process of realizing the higher goals of society. In doing the right things, policy makers choose a mix of Intermediate outputs maximizing their preference value for public service outcomes, while managers do things right when responsible for producing outputs efficiently. This distinction enables us to pinpoint important reasons for inefficiencies in the provision of public services. Taking advantage of the method of scenario based planning, a model for measuring effectiveness is developed for situations where traditional methods such as two-stage regressions fail due to long time lags and lack of variation in the variables. Scenarios take the role of outcomes in the modeling of outcome mapping functions, where each scenario represents a set of environmental variables. The model is specified for the provision of defense outcomes, where the lag between changes in input and impacts on outcomes are significant. From a sample of 12 combat units in the Norwegian Armed Forces, producing different outputs, we find that inefficiencies in output mix can explain most of the changes in overall effectiveness over a four-year period of time.
Keywords: D24; H40; C60; 330; output mix efficiency; Efficiency; DEA; Military